Efficacy of acupuncture as adjunctive therapy for patients with acute exacerbation of chronic obstructive pulmonary disease: a systematic review and meta-analysis - Li, Guofeng; Liu, Jimin; Yang, Guixian; Li, Jiajia; He, Yuan; Fei, Xinru; Wei, Lai; Zhao, Dongkai (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a highly prevalent and potentially fatal respiratory condition. Acute exacerbations can accelerate lung function decline and increase mortality. Acupuncture has been increasingly used as an adjunctive treatment for respiratory diseases, but its effectiveness in acute exacerbations of COPD (AECOPD) remains controversial. Existing evaluations on this topic are limited in scope and depth. This study aimed to provide a more comprehensive review to evaluate the effectiveness of acupuncture as an adjuvant treatment for acute exacerbations of chronic obstructive pulmonary disease.Study designSystematic review and meta-analysis of existing randomized controlled trials on acupuncture-assisted treatment of acute exacerbation of chronic obstructive pulmonary disease (AECOPD).MethodsWe included randomized controlled trials (RCTs) comparing acupuncture combined with conventional Western medicine to conventional Western medicine alone in patients with acute exacerbations of COPD (AECOPD). Our literature search covered ten databases, including PubMed and Web of Science ect., up until March 2025. The primary outcome was the effective rate, while secondary outcomes included lung function (FEV1%, FEV1/FVC%, FEV1), arterial blood gas analysis (PaO2, PaCO2, SaO2), the 6-min walk test (6MWT), COPD Assessment Test (CAT), modified Medical Research Council (mMRC) scale, and success rate of weaning. Data were extracted from eligible studies, and statistical analysis was performed using RevMan 5.3 and Stata 16.0. Risk of bias and evidence quality were assessed using Cochrane tools and GRADE methodology.ResultsThe study included 31 randomized controlled trials (RCTs) with 2,299 participants. The studies were primarily conducted in hospital inpatient departments, and the typical treatment duration ranged from 1 to 2 weeks. Compared with conventional Western medicine alone, acupuncture combined with conventional Western medicine showed greater effectiveness (RR = 1.23, 95%CI 1.17 1.29, p < 0.001). Acupuncture significantly improved lung function (FEV1%: MD = 5.67, 95%CI 2.97 8.37, p < 0.001; FEV1/FVC: MD = 4.44, 95%CI 1.86 7.03, p < 0.001; FEV1: MD = 0.37, 95%CI 0.26 0.47, p < 0.001), reduced hypoxia (PaO2: MD = 3.60, 95%CI 2.23 4.98, p < 0.001; PaCO2: MD = -3.30, 95%CI -5.80 −0.80, p < 0.05; SaO2: MD = 4.23, 95%CI 3.02 5.43, p < 0.001), and improved exercise tolerance (6MWT: MD = 40.34, 95%CI 30.50 50.17, p < 0.001), quality of life (CAT: MD = -2.68, 95%CI -3.39 −1.96, p < 0.001), and dyspnea (mMRC: MD = -0.33, 95%CI -0.47 −0.20, p < 0.001). However, the weaning success rate did not show a statistically significant difference between the two groups (RR = 1.18, 95%CI 0.95 1.48, p = 0.14). Mild side effects were reported in some studies. We rated the quality of evidence as very low to medium.ConclusionThis systematic review and meta-analysis demonstrate that acupuncture, as an adjunctive treatment for acute exacerbations of chronic obstructive pulmonary disease, improves clinical efficacy and key outcomes. Our findings are consistent with previous studies that demonstrated improvements in the COPD Assessment Test (CAT) and arterial blood gas parameters (PaO2 and PaCO2). Unlike previous meta-analyses, the present study showed that adjunctive acupuncture significantly improved patient lung function FEV1% outcomes and significantly improved patient 6-min walk distance and modified Medical Research Council (mMRC) score; however, there was no significant difference in the success rate of weaning between the two groups. Although the review highlights clinical benefits, the heterogeneity of the included studies and the overall quality of the evidence suggest that more high-quality randomized controlled trials are needed to validate these findings and optimize treatment strategies. These studies should also prioritize standardizing acupuncture regimens, extending treatment duration, and conducting long-term follow-up assessments.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/ ID:CRD42024528155.